PENERAPAN METODE LESSON STUDY DALAM MELATIH KETERAMPILAN DASAR MENGAJAR MAHASISWA PGSD UTM: Array - Amalia Nugraha Fisabilila; Nilamsari Damayanti Fajrin (eductum: Jurnal Literasi Pendidikan, 2022)
The pandemic COVID-19has caused learning to be conducted online to minimize face-to- face interactions so that PGSD students experience limitations in implementing basic teaching skills. The purpose of this study is to measure the effectiveness of themethod lesson study in equipping PGSD students who are able to develop learning planning tools, but have never practiced teaching because of thepandemic COVID-19. This research is a descriptive qualitative research that is based on data during observation and application. In this study using themethod lesson study which is classified as action research. This research consists of three stages, namely the planning stage, the implementation stage, and the reflection stage. In the application of lesson study, students work in pairs and take turns as model teachers and observers . The result of this study is to prove that themethod lesson study can effectively train basic teaching skills for PGSD UTM students.